2017
DOI: 10.1126/science.aao2109
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of surface lattice oxygen in single-atom Pt/CeO 2 for low-temperature CO oxidation

Abstract: To improve fuel efficiency, advanced combustion engines are being designed to minimize the amount of heat wasted in the exhaust. Hence, future generations of catalysts must perform at temperatures that are 100°C lower than current exhaust-treatment catalysts. Achieving low-temperature activity, while surviving the harsh conditions encountered at high engine loads, remains a formidable challenge. In this study, we demonstrate how atomically dispersed ionic platinum (Pt) on ceria (CeO), which is already thermall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

58
1,044
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,270 publications
(1,108 citation statements)
references
References 36 publications
(52 reference statements)
58
1,044
3
3
Order By: Relevance
“…[58] In contrast, as tudy of B-and N-doped carbon supports indicated that anionic Au species formed in the presence of boron were more active because CO was less strongly adsorbed than it would otherwise be on Au cations. [12] Polyhedral ceria nanorods were shown to effectively stabilize SAs with higher metal content than q-Al 2 O 3 , [95] but the low-temperature activity was also limited, which was attributed to inactive lattice oxygen and the strong binding of CO molecules to Pt ions.T he performance could be drastically improved by steam treatment at 1023 K, thereby reducing the temperature required to reach 100 %c onversion by > 150 K. [14] This was attributed to the activation of surface oxygen generating hydroxy groups,which differed from those formed upon co-feeding water during the reaction. [93] Themain kinetic pathway and catalytically active sites on Au/TiO 2 are anticipated to be highly dependent on the temperature and oxygen partial pressure,a nd the activity dominated by at ransient Au À CO species under oxidizing conditions and T < 400 K. [94] Thed ynamic formation of SAs from small nanostructures under reaction conditions was also proposed to account for the distinctive size effect apparent over Au/CeO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[58] In contrast, as tudy of B-and N-doped carbon supports indicated that anionic Au species formed in the presence of boron were more active because CO was less strongly adsorbed than it would otherwise be on Au cations. [12] Polyhedral ceria nanorods were shown to effectively stabilize SAs with higher metal content than q-Al 2 O 3 , [95] but the low-temperature activity was also limited, which was attributed to inactive lattice oxygen and the strong binding of CO molecules to Pt ions.T he performance could be drastically improved by steam treatment at 1023 K, thereby reducing the temperature required to reach 100 %c onversion by > 150 K. [14] This was attributed to the activation of surface oxygen generating hydroxy groups,which differed from those formed upon co-feeding water during the reaction. [93] Themain kinetic pathway and catalytically active sites on Au/TiO 2 are anticipated to be highly dependent on the temperature and oxygen partial pressure,a nd the activity dominated by at ransient Au À CO species under oxidizing conditions and T < 400 K. [94] Thed ynamic formation of SAs from small nanostructures under reaction conditions was also proposed to account for the distinctive size effect apparent over Au/CeO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[10] Aided by synthetic and analytical advancements,ahuge range of potential host materials has now been reported (Figure 2), which encompasses metal oxides, [11][12][13][14] metal hydroxides, [15,16] metals (also termed single-atom alloys (SAAs)), [17,18] micro/ mesoporous materials such as zeolites, [19,20] metal-organic frameworks (MOFs), [21,22] silicas, [23,24] carbon-based materials, [25][26][27][28] organopolymers, [29,30] nitrides, [31][32][33] and carbides. [10] Aided by synthetic and analytical advancements,ahuge range of potential host materials has now been reported (Figure 2), which encompasses metal oxides, [11][12][13][14] metal hydroxides, [15,16] metals (also termed single-atom alloys (SAAs)), [17,18] micro/ mesoporous materials such as zeolites, [19,20] metal-organic frameworks (MOFs), [21,22] silicas, [23,24] carbon-based materials, [25][26][27]…”
Section: Properties Of Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another hint of the importance of water comes from the recent work of Datye and coworkers [46], who have shown that pre-treatment of a Pt/CeO 2 catalyst with steam results in a highly active SAC system. They propose OH bound at Pt 2+ centres to be directly involved in the CO oxidation mechanism, and their DFT-determined reaction pathway (shown in Fig.…”
mentioning
confidence: 99%
“…A legend for the atom colours is shown in the inset.Figure reproduced with permission from Ref. [46] …”
mentioning
confidence: 99%